Determinants of diabetes comorbidities in Indonesia: a cohort study of non-communicable disease risk factor - Kristanti, Dewi; Rahajeng, Ekowati; Sulistiowati, Eva; Kusumawardani, Nunik; Dany, Frans (Universa Medicina, 2021)
BackgroundType 2 diabetes mellitus (DM) is a non-communicable disease that constitutes a huge health burden, with the presence of comorbidities of DM adding to it. This study aimed to obtain the main determinants of the combined incidence of DM and its main comorbidities in adults.MethodsThis was a further analysis of the Non-Communicable Disease Risk Factor Cohort Study 2011 – 2018 involving 3730 subjects. Data of diabetes-free respondents at baseline were followed up every 2 years for 6 years. Data collection was carried out through interviews and health examinations. All subjects were assayed for blood glucose and lipid parameters. Chi-square test and Cox regression were implemented for data analysis.ResultsDuring 6 years of follow-up, DM incidence occurred in 567 (15.2%) subjects. The most common comorbidities were increased low density lipoprotein (LDL), central obesity, increased total cholesterol, obesity and hypertension. Most of the comorbidities occurred before the diagnosis of DM incidence. The determinants of the combined DM incidence–increased LDL are obesity, hypertension, and a family history of DM. The determinants of the combined DM incidence–central obesity are increased triglycerides, hypertension, male gender, and family history of DM. While the determinants of the combined DM incidence–hypertension are obesity and increased triglycerides.CONCLUSIONThis study demonstrated a high burden of diabetes incidence with comorbidities among adults. Knowledge of the magnitude of the diabetescomorbidity determinants emphasizes the role of non pharmacological intervention such as weight reduction and dietary modification.